The Comparison of Translation Strategies in the Old and New Translations of The 100: A Ranking of the Most Influential People in History by Michael Hart - Nayla, Ananda; Dewi, Haru Deliana (Universitas Sanata Dharma, 2024)
Translations of the same text might be different from one version to another based on the translation strategies that are used by the translator. By examining the translation strategies in the old and the new translations of a book titled The 100: A Ranking of the Most Influential People in the World, this research aims to analyze the different translation procedures, methods, and ideologies used in the two versions. To conduct this research, the researcher uses the descriptive qualitative method with a purposive sampling technique. This research focuses on analyzing the first chapter about the biography of Prophet Muhammad and the fifth chapter about the biography of Confucius. The findings show that nine translation procedures are used in both the old and the new translations. However, there is a difference in the dominant translation procedure and the frequency of the overall translation procedures. The dominant procedure in the old translation is expansion, while in the new translation is naturalization. The total frequency of the procedures in the new translation is also not as many as in the old translation. Based on the procedures found, the old translation uses the communicative translation method and free translation method, while the new translation uses the faithful translation method and semantic translation method. This result shows that there is a shift of ideology between the old and the new translations, from domestication to foreignization.